The effect of durable goods and ICT on euro area productivity growth? - Jukka Jalava; Ilja Kristian Kavonius (European Central Bank (ECB), 2008)
The present System of National Accounts (SNA93) treats durable consumption goods as consumption goods rather than investment although rentals for owner occupied households is imputed into GDP. We argue that households de facto treat the purchase of durable goods as investments and thus, the treatment of durables as capital assets conceptually does not differ from the present treatment of owner occupied dwellings. This is not captured by the economic analysis based on current statistical conventions. The purpose of this paper is to estimate the effect of durable goods and ICT on euro area economic growth and productivity change; when expenditure on consumer durables is recorded as capital investment. The capitalization of consumer durables impacts both the levels and growth rates of the capital stock, productivity and GDP. Our growth accounting computations demonstrated that the capital services of durables contributed one-tenth of economic growth and one-eight of labour productivity growth in 1995-2004. ICT's impacts were larger, i.e., one-fifth of GVA growth and one-sixth of labour productivity growth.
Keywords: E01; E21; E22; J24; O11; 330; asset; durable good; household production; ICT; productivity; technological transformation; user cost; Dauerhafte Konsumgüter; Investitionsstatistik; Nationaleinkommen; Informationstechnik; Produktivität; Haushaltsproduktion; EU-Staaten